Resistance Patterns in Second-Line Sensitization Tests and Their Effect on MDR-TB Treatment Success in Relapsed and Failed Cases - Kunarisasi, Sity (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Tuberculosis recurrence is caused by reinfection with Mycobacterium tuberculosis that has already been experienced or infection with a new strain of bacteria. The increasing incidence of TBMDR in the community accelerates the spread of TBMDR. Objective: To identify TBMDR treatment failure in relapse cases, and category 1 and 2 treatment failure. Method: Retrospective. Secondary data from the Ministry of Health SITB, 2017-2019 period shows that the sample size of relapses, category 1 and 2 treatment is 466 patients. Results: the relapse bivariate test and treatment failure categories 1 and 2 obtained a p-value of <0.05 (age 17-about 60 years and second-line sensitivity test). They are affected by HIV status. The regression results of the second sensitization test strongly influenced TB-relapsed patients to fail, dropout, and complete treatment compared to cured treatment patients, still-relapsed 17-44 years old patients, and category 1 and 2 treatment failure were more likely to be LFU than recover, and the second sensitivity test affected treatment failure and completion rather than recovery, although HIV status did not affect treatment outcomes. Conclusion: Strategy to reduce the rate of recurrence and conversion failure by examining genetic mutations (biomarkers) of M. tuberculosis. Keywords: Relapse, treatment failure, sensitization test, outcome treatment.